Influence of increase of sensomotor task difficulty on neural system arousal and motoric performance - Benešová, Daniela; Švátora, Karel (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Requirements of current everyday life underline the importance of accurate and rapid response to the created situation. In addition to our ability to physically handle movement responses, it is very important to decide, which type of movement response is selected, and how a particular movement is programmed so that the movement response to the created situation could be adequate. If the difficulty of a sensomotor task is higher, the time needed to achieve the goal is extended – this fact was explored by Fitts already in 1954. Aim of Study. The objective of this study was to find out whether an increase in the difficulty of a performed movement task with certain demands on perception, thinking, attention, and memory can influence activation of the nervous system, and vice versa. Material and Methods. The test sample consisted of 84 persons (n = 84). The activation level of the nervous system was objectified by the measurement of skin conductivity with the device PowerLab, ML 116 GSR Amp from ADInstrument. The level of sensomotor performance was verified by the support drawing test. Results. The Friedman test result shows that there a significant difference exists in performance results in at least one measurement of the support drawing test. It is obvious from the table that the average values of time in all three measurements of the support drawing test are increasing. The effect size value of η2 = 1.16 shows that, almost with a good degree of certainty, the result is not influenced by statistics tools. Conclusions. This research confirmed our expectations that the increased difficulty level of a sensomotor test of bimanual co-ordination has a significant impact on sensomotor performance, as well as on changes in activity of the autonomic nervous system. This study has a limited validity for the college student population at the age of 20-25 years.
Keywords: performed movement task; sensomotor test; nervous system